MDR1 gene polymorphisms and P-glycoprotein expression in respiratory diseases - Milojkovic, Maja; Milacic, Nena; Radovic, Jelena; Ljubisavljevic, Srdjan (Biomedical papers, 2015)
Background: P-glycoprotein (P-gp/MDR1), a member of the ATP-binding cassette (ABC) transporters super family, encoded by the ABCB1/MDR1 gene, is one of suggested respiratory tract protection components, found in various tissues with a barrier function, such as tracheobronchial epithelium and lung parenchyma. As an ATP-dependent pump, P-gp extrudes lipophilic particles out of cells and acts as a gatekeeper against numerous xenobiotics, with a protective role in mediating DNA damage, secretion of toxic compounds, apoptosis and the immune response. Therefore, a presence of MDR1 polymorphisms and altered P-gp expression may be important for pathogenesis of reduced lung inflammatory response on cigarette smoke exposure, as well as for the severity of chronic obstructive pulmonary disease and lung cancer pathogenesis and treatment efficacy.Methods and Results: We have analyzed data available from experimental and clinical studies performed to establish the role of MDR1 polymorphisms, especially the 3435C>T variation, and P-gp expression in pathogenesis and clinical outcome of human respiratory diseases.Conclusions: Although there are indications that altered expression of P-gp and/or polymorphisms of MDR1 gene play an important role in respiratory diseases pathogenesis and treatment, their exact role and relevance are insufficiently investigated, with exception of certain chemotherapeutic agents' efficacy in lung cancer treatment. Further research in this field, including bigger series of patients, is necessary for better understanding of respiratory diseases' pathogenesis and treatment.
Keywords: P-gp expression; MDR1 polymorphisms; respiratory diseases; COPD; lung cancer